ТҮРКИЙ ФОЛЬКЛОРТАНЫЎДА АҢЫЗЛАРДЫҢ ИЗЕРТЛЕНИЎИ ҲАҚҚЫНДА - Елмуратов, Р.Х. (SCIENCE and SOCIETY, 2022)
This article deals with the research of specific features of legends, one of the genres of folklore and comparative analysis of scientific works of Turkic and world study of folklore on legends, their typological similarities and differences are also described.